Laboratory testing of Malaysian rocks according to ISRM suggested methods / Azami Zainal Abidin - Zainal Abidin, Azami (1993)
The purpose of the study is to tabulate data of engineering properties of Malaysian rocks by carrying out a series of laboratory tests as recommended by ISRM suggested method. The ultimate objective is to obtain, rocks properties and Laboratory Field Index as recognised by ISRM. Since most engineering properties test such as physical properties, hardness and abrasiveness, sound velocity, tensile strength, shear strength, point load index, Schmidt rebound hardness etc, are rather elaborate and time consuming and involve tedious specimen preparations, an attempt is made to correlate index properties of rocks to their engineering properties.